Outcome of Gestational Diabetes during Pregnancy and at Delivery - Hiba Arshad Shaikh, Sharin Khan, Ayesha Mustafa, Asma Ali Depar, Bakhtawar Mateen, Muhammad Taha Arshad Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Gestational diabetes (GDM) is a state of intolerance to glucose that initiates or is first diagnosed during gestation. About 1-14% of all pregnancies are complicated by GDM. The pregnancy-related morbidity and mortality in gestational diabetes is lower than in overt diabetes; however, if left untreated, it is significantly higher than in nondiabetic women. Treating GDM is important because appropriate treatment reduces side effects on the mother and newborn. GDM during pregnancy has a number of adverse short- and long-term consequences for both the mother and the fetus. Aim: To establish the relationship between gestational diabetes and complications related to pregnancy and childbirth. Study Design: A prospective cohort study. Place and Duration: The study was conducted at the Karachi Aga Khan University Hospital in the Department of Obstetrics and Gynecology from 22 November, 2018 to 22 May 2019, six months after the approval of the study. Methods: 130 patients, 65 patients in the GDM group and 65 patients in the non-GDM group were enrolled in the study. Demographic data were presented as standard deviation and mean as well as simple descriptive statistics, while qualitative variables as percentage and frequency. Chi-square test was applied for comparison of the incidence of complications related to pregnancy and childbirth. P<0.05 was considered statistically significant. Relative risk was calculated. Results: 130 total patients, including 65 patients in GDM group and 65 patients in non GDM group were included. Mean age in GDM and non GDM group was 29.27±2.79 years and 28.49±3.40 years. Outcome of pregnancy in GDM and non GDM group showed that 27 (41.5%) and 18 (27.7%) had pregnancy induced hypertension, 07 (10.8%) and 03 (4.6%) had pre-eclampsia, 29 (44.6%) and 07 (10.8%) had polyhydramnios, 04 (6.2%) and 02 (3.1%) had antepartum hemorrhage, 01 (1.5%) and 06 (9.2%) had premature rupture of membrane, 11 (16.9%) and 09 (13.8%) had preterm labour, 13 (20%) and 04 (6.2%) had urinary tract infection. Outcome of pregnancy in GDM and non GDM group showed 51 (78.5%) and 33 (50.8%) had induction of labour, 17 (26.2%) and 14 (21.5%) had low birth weight, 14 (51%) and 03 (4.6%) had macrosomia, 02 (3.1%) and 01 (1.5%) had birth injury and 10 (15.4%) and 11 (16.9%) had NICU admission. Conclusion: Gestational diabetes (GDM) is the utmost communal medicinal complication of pregnancy. It has negative consequences for the mother and the newborn baby. Maintaining glycemia in GDM decreases the morbidity of both baby and mother. Keywords: Gestational diabetes mellitus, delivery outcome, pregnancy outcome, maternal and fetal outcomes.